Pengelolaan Sarana Pendidikan di SMK Negeri 1 Sumatera Barat - Antika Rissya; Irsyad Irsyad; Ahmad Sabandi; Sulastri Sulastri (Journal of Educational Administration and Leadership, 2020)
This research is based on the results of the author's observations at the Vocational High School (SMK) Negeri 1 West Sumatra which shows that the management of educational facilities is still not good. The purpose of this study was to obtain data and information about the management of educational facilities seen from the aspects of (1) planning, (2) procurement, (3) storage, (4) inventory, (5) distribution, (6) maintenance. This type of research is descriptive with a population of 19 people as the Deputy for Facilities and Infrastructure, Head of Administration, Asset Manager, Head of Expertise Program, and Head of Workshop. The research instrument used a questionnaire with a Likert scale model. The results showed that: (1) The management of educational facilities seen from the aspect of planning had been carried out well 4.38, (2) the management of educational facilities seen from the aspect of procurement had been carried out well 3.93, (3) the management of educational facilities in terms of aspects Storage has been carried out well 4,14, (4) Management of educational facilities seen from the aspect of inventory has been carried out well 4,15, (5) management of educational facilities seen from the aspect of distribution has been carried out well 4,49, (6) management of facilities Education seen from the aspect of maintenance has been carried out well 4,31. Overall, it can be concluded that the Management of Educational Facilities in Vocational High School (SMK) Negeri 1 West Sumatra is in the good category with an average score of 4.23.